The Influence of Price Earning Ratio (PER), Earning Per Share (EPS), Debt To Equity Ratio (DER) and Cash Dividend Policy on Stock Prices of Companies Listed on the IDX(Study on Consumer Goods Sector Companies for the Period 2019-2022) - Novita Yura; Jullie J. Sondakh; Claudia W. M. Korompis (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
This study aims to analyze the impact of Price Earning Ratio (PER), Earnings Per Share (EPS), Debt to Equity Ratio (DER), and Cash Dividend Policy on the stock prices of companies listed on the Indonesia Stock Exchange (IDX), focusing on the Consumer Goods sector for the 2019-2022 period. This research adopts a quantitative approach utilizing secondary data. The sampling technique used is purposive sampling, a non-probability sampling method, which resulted in 23 selected companies from a total of 119. The data were analyzed using descriptive statistical analysis, classical assumption tests, multiple linear regression, and hypothesis testing with IBM SPSS version 26. The findings indicate that PER, EPS, and cash dividends significantly influence stock prices, suggesting that strong financial performance and consistent dividend distribution enhance investor confidence. Conversely, DER does not show a significant effect, implying that the company's capital structure does not directly impact stock price fluctuations in the Consumer Goods sector. These findings provide valuable insights for investors and financial managers in making informed investment decisions.